Approximation of Random Fixed Point Theorems - Salahuddin, (Discontinuity, Nonlinearity, and Complexity, 2026)
The aim of this paper is to establish and discuss the approximation of Caristi’s random fixed point theorems. Our theorem is used to determine a large numbers of nonlinear stochastic problems.